â€œKebijakan Jepang Untuk Meningkatkan Pariwisata Melalui Sertifikasi Halal Foodsâ€ Japan Policy to Improve Tourism Through Halal Foods Certification - Muhammad Toha Eka Prasetia (HI 16 UMY 077, 2016)
*77 This thesis is contained about Japan policy to improve tourism sector through halal food certification. As the tiger of Asia, who has the highest GDP and technology level, Japan was known as a wealthiest country in Asia. But, right now the situation is changed. Recession made Japan experienced economic downturn. In order to make thing is up and recovery, Japan needs a new sector to backup the deflation. And the way to make the economic recovery and sustain, Japan Government has another sector, that is tourism sector. tourism sector in Japan is now getting rise, and that means opportunity for Japan to recover. In this case, tourist is not only dealing with one culture, but of course it will across culture, And Muslim tourism is one of the challenge in order to improve tourism sector, and to serve a good service